INTERJEKSI DALAM TALKSHOW â€œPAGI-PAGI PASTI HAPPYâ€ DI TRANS TV - Azwar, Sri Rahmaddona; Agustina, Agustina (Jurnal Bahasa dan Sastra, 2019)
The purpose of this study was to describe the forms of interjection, types of interjection and functions of interjection in the â€œPagi-Pagi Pasti Happyâ€ (PPPH) talkshow on Trans TV. This type of research was a qualitative study using descriptive methods by explaining the meaning behind the presenter's speeches related to interjection. The results of this study were firstly, the form of interjection in PPPH consists of two forms of interjection, namely the basic form and the derivative form. Types of interjection in PPPH program on Trans TV consists of three types of interjection, i.e. a attitude, positive, and neutral attitude Third, the function of the interjection found consists of eight functions, namely as exclamation, wonder, pain, sadness, disappointment, admiration, relief, and disgust.Keywords: form, type, function of interjection, pragmatics, Pagi-Pagi Pasti Happy